Seductive Atmospheres, Conflicting Symbols: Religious Landmark Buildings in Diverse Societies - Steets, Silke (Eurostudia, 2017)
Informed by the sociology of knowledge, this paper understands buildings as “material objectivations” that continuously “act back” upon their users. It examines the following question: Why are the discussions about constructing new (religious) landmark buildings, or the rebuilding of historical ones, so emotionally charged? Using the debate about a proposed golden cross on top of the reconstruction of the Prussian City Palace in Berlin as a starting point, this article studies buildings on two levels: the level of bodily experience, on which they unfold their seductive features, and the level of – often conflicting – symbolic inscription. The analysis shows that religious landmark buildings, such as churches or mosques, use specific means of expression to stimulate the experience of the “numinous.” As a result, they are often loaded with strong emotions and feelings of belonging or dis-belonging. As religious communities increasingly become fragmented in diverse societies, symbolic recognition in landmark projects appears to be a deeply political concern.